Design, installation, and initial operating experience with line drop compensation at John Day powerhouse. - Kosterev, D. (IEEE Transactions on power systems)
This paper describes design, installation, testing, and initial operating experience with line drop compensation (LDC) at John Day powerhouse. The voltage stability analysis is performed to quantify the system benefit provided by John Day LDC, transient stability studies are performed to determine target levels for LDC settings. The design, which utilizes both reactive current droop compensation and line drop compensation, is described. LDC installation and testing are presented. Operating experience is discussed, and LDC benefit for system disturbances is demonstrated